2014
DOI: 10.1128/aac.02744-13
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Activity of Plazomicin against 5,015 Gram-Negative and Gram-Positive Clinical Isolates Obtained from Patients in Canadian Hospitals as Part of the CANWARD Study, 2011-2012

Abstract: Plazomicin is a next-generation aminoglycoside that is not affected by most clinically relevant aminoglycoside-modifying enzymes. The in vitro activities of plazomicin and comparator antimicrobials were evaluated against a collection of 5,015 bacterial isolates obtained from patients in Canadian hospitals between January 2011 and October 2012. Susceptibility testing was performed using the Clinical and Laboratory Standards Institute (CLSI) broth microdilution method, with MICs interpreted according to CLSI bre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
74
0
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 109 publications
(80 citation statements)
references
References 23 publications
2
74
0
4
Order By: Relevance
“…No significant differences were found between agar dilution MICs and microdilution MICs (MIC 50 , 0.5 mg/liter; MIC 90 , 1 mg/liter; MIC range, 0.125 to 4 mg/liter). Our findings are consistent with previous studies that showed plazomicin to be highly active against MDR clinical isolates of Enterobacteriaceae, including ESBL-producing E. coli isolates (15,16).…”
supporting
confidence: 83%
“…No significant differences were found between agar dilution MICs and microdilution MICs (MIC 50 , 0.5 mg/liter; MIC 90 , 1 mg/liter; MIC range, 0.125 to 4 mg/liter). Our findings are consistent with previous studies that showed plazomicin to be highly active against MDR clinical isolates of Enterobacteriaceae, including ESBL-producing E. coli isolates (15,16).…”
supporting
confidence: 83%
“…Similarly, the broad-spectrum agent eravacycline (a new fluorocycline) also lacks activity against A. baumannii, B. cenocepacia, and P. aeruginosa (949,952). Plazomicin is a new aminoglycoside derivative of sisomicin with significant activity against a range of Gram-positive and Gram-negative bacteria (including multidrug-resistant isolates) (953,954). However, its activity is adversely affected by increased efflux in A. baumannii and P. aeruginosa (955).…”
Section: Multidrug Efflux Pumps As a Challenge In Drug Developmentmentioning
confidence: 99%
“…Natural product β-lactams, macrolides, tetracyclines, aminoglycosides, and glycopeptides have all been the subject of derivatization leading to newer generations of antibiotics. Steady progress in the clinical development of the aminoglycoside plazomicin, 6 the tetracycline eravacycline, 7 and the cephalosporin ceftolozane 8 for the treatment of Gram-negative infections is a recent reminder that chemical modification of established classes of natural products is still a viable route for drug discovery.…”
mentioning
confidence: 99%